Physicochemical and ion-binding properties of highly aliphatic humic substances extracted from deep sedimentary groundwater. Issue 8 (13th July 2015) - Saito, Takumi; Terashima, Motoki; Aoyagi, Noboru; Nagao, Seiya; Fujitake, Nobuhide; Ohnuki, Toshihiko
Abstract : We have revealed distinctive physicochemical and ion-binding properties of humic and fulvic acids from deep sedimentary groundwater. Abstract : Humic substances (HSs) are ubiquitous in various aquatic systems and play important roles in many geochemical processes. There is increasing evidence of the presence of HSs in deep groundwater; nevertheless, their ion binding properties are largely unknown. In this study we investigated the physicochemical and ion-binding properties of humic and fulvic acids extracted from deep sedimentary groundwater. The binding isotherms of protons (H + ) and copper (Cu 2+ ) were measured by potentiometry and fitted to the NICA-Donnan model, and the obtained parameters were compared with the generic parameters of the model, which are the average parameters for HSs from surface environments. The deep groundwater HSs were different from surface HSs, having high aliphaticities, high sulfur contents, and small molecular sizes. Their amounts of acidic functional groups were comparable to or slightly larger than those of surface HSs; however, the magnitude of Cu 2+ binding to the deep groundwater HSs was smaller. The NICA-Donnan model attributed this to the binding of Cu 2+ to chemically homogeneous low affinity sites, which presumably consist of carboxylic groups, via mono-dentate coordination at relatively low pH. The binding mode tended to shift to multi-dentate coordination with carboxylic groups and more heterogeneous alcoholic/phenolic groups at higher pH. X-ray absorption spectroscopy also revealed that Cu 2+ binds to O/N containing functional groups and to a lesser extent S containing functional groups as its divalent from. This study shows the particularity of the deep groundwater HSs in terms of their physicochemical and ion-binding properties, compared with surface HSs.